RUSSIA IN THE BOLOGNA PROCESS: GOAL - TO ENHANCE THE COMPETITIVENESS OF HIGHER EDUCATION - N. R. Kamynina; A. O. Grudzinskiy (Высшее образование в России, 2017)
The article discusses a modern understanding of the goals of the participation of the Russian Federation in the Bologna Process and the European Higher Education Area (EHEA). Currently, the main goal is to enhance the international competitiveness of Russian higher education, among other things, in order to foster the development ofthe export of educational services. The authors present a retrospective review of publications on the subject of the Bologna process and the reform of the higher education system in Russia; provide an overview of the evolution of the views on the problem, taking into account the changing approaches to the identification of Russian higher education in the international context from declarative postulates to the application of criteria used in internationally recognized university ranking systems; and provide information on Russia's participation in the governance of the EHEA since 2015.